Mesophyll conductance does not contribute to greater photosynthetic rate per unit nitrogen in temperate compared with tropical evergreen wet-forest tree leaves - Bahar, Nur H A (The New phytologist, 2018)
© 2018 The Authors. New Phytologist © 2018 New Phytologist Trust.